Battery

By integrating an elastic spacer with fibers and voids into the battery structure to absorb the expansion and contraction of the power generation element, the issue of reduced charge and discharge capacity in solid lithium-ion batteries is addressed, ensuring maintained battery performance over repeated cycles.

JP7666403B2Active Publication Date: 2025-04-22TOYOTA JIDOSHA KK
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2022084591
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-05-24
Publication Date
2025-04-22
Estimated Expiration
2042-05-24

AI Technical Summary

Technical Problem

Solid lithium-ion batteries using metallic lithium as the negative electrode active material experience expansion and contraction with charge and discharge, leading to peeling between components and a reduction in charge and discharge capacity over repeated cycles.

Method used

Incorporating an elastic spacer with fibers and voids, laminated in the stacking direction of the battery elements, to absorb the expansion and contraction of the power generation element, thereby reducing mechanical stress and maintaining battery performance.

Benefits of technology

The use of an elastic spacer with fibers and voids effectively suppresses the decrease in charge and discharge capacity due to repeated charging and discharging, maintaining battery performance by allowing elastic deformation in response to the power generation element's expansion and contraction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666403000002
    Figure 0007666403000002
  • Figure 0007666403000003
    Figure 0007666403000003
  • Figure 0007666403000004
    Figure 0007666403000004
Patent Text Reader

Abstract

To provide a battery capable of preventing the reduction of charge / discharge capacity due to repeated charging / discharging.SOLUTION: A disclosed battery includes: a battery element in which a positive electrode current collector layer, a power generation element, and a negative electrode current collector layer are laminated in this order; and an elastic spacer laminated in the laminate direction of the battery element. The power generation element expands and contracts in the laminate direction as it charges and discharges, and the elastic spacer contains fibers and has voids. Regarding the stacking direction, in the power generation element, the positive electrode layer, a solid electrolyte layer, and the negative electrode layer are laminated in this order at least in the charging state.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to batteries. [Background technology]

[0002] Patent Document 1 discloses a bipolar battery comprising a battery element formed by alternately stacking a predetermined number of bipolar electrodes, each having a positive electrode layer formed on one surface of a current collector and a negative electrode layer formed on the other surface, and electrolyte layers that perform ion exchange between the bipolar electrodes, and a stack thickness absorbing member interposed between the battery elements to absorb distortion in the stacking direction.

[0003] Patent Document 2 discloses a lithium ion secondary battery having a positive electrode and a negative electrode on either side of a solid electrolyte and current collectors on the outside of the positive electrode and the negative electrode, respectively, characterized in that at least one of the current collectors contains a viscoelastic material. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2007-26734 A [Patent Document 2] JP 2009-181874 A Summary of the Invention [Problem to be solved by the invention]

[0005] For example, a solid-state lithium ion battery, more specifically, a solid-state lithium ion battery using metallic lithium as a negative electrode active material, may expand and contract during charging and discharging. Such expansion and contraction of the battery may cause peeling between components of the battery, such as a current collector layer and an electrode layer, and as a result, the charge and discharge capacity may decrease when the battery is repeatedly charged and discharged.

[0006] An object of the present disclosure is to provide a battery capable of suppressing a decrease in charge / discharge capacity due to repeated charging and discharging. [Means for solving the problem]

[0007] The present inventors have found that the above object can be achieved by the following means: Aspect 1 The battery includes a battery element in which a positive electrode current collector layer, a power generating element, and a negative electrode current collector layer are laminated in this order, and an elastic spacer is laminated in the lamination direction of the battery element, The power generating element expands and contracts in the stacking direction as the element is charged and discharged, The elastic spacer contains fibers and has voids. battery. Aspect 2 With respect to the stacking direction, the power generating element has a positive electrode layer, a solid electrolyte layer, and a negative electrode layer stacked in this order at least in a charged state. 2. The battery of embodiment 1. Aspect 3 3. The battery of claim 2, wherein the negative electrode layer contains lithium as a negative electrode active material that is deposited between the solid electrolyte layer and the negative electrode current collector layer in a charged state. Aspect 4 4. The battery of any one of aspects 1 to 3, wherein the fibers are carbon fibers. Aspect 5 The battery of any one of aspects 1 to 4, wherein the elastic spacer is a compression-molded body of the fiber. Aspect 6 The battery of any one of aspects 1 to 5, wherein the ratio of the fibers to the solid content of the elastic spacer is 90 volume % or more. Aspect 7 7. The battery according to any one of aspects 1 to 6, wherein the elastic spacer has a porosity of 60 to 80%. Aspect 8 8. The battery of any one of aspects 1 to 7, wherein the elastic spacer has an elastic range of 0.1 or more. Aspect 9: The battery of any one of embodiments 1 to 8, which is a lithium ion battery. Effect of the Invention

[0008] According to the present disclosure, it is possible to provide a battery capable of suppressing a decrease in charge / discharge capacity due to repeated charging and discharging. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic diagram of a solid-state battery 1 according to a first embodiment of the present disclosure. [Diagram 2] FIG. 2 is a top view of the test all-solid-state battery 2. [Diagram 3] FIG. 3 is a cross-sectional side view of the test all-solid-state battery 2 in a discharged state. [Figure 4] FIG. 4 is a cross-sectional side view of a test all-solid-state battery 2 in a charged state. [Diagram 5] FIG. 5 is a schematic diagram showing a measurement device 3 for measuring pressure during charging and discharging of a test all-solid-state battery 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the present disclosure will be described in detail. Note that the present disclosure is not limited to the following embodiments, and various modifications can be made within the scope of the present disclosure.

[0011] The battery of the present disclosure has a battery element in which a positive electrode current collector layer, a power generating element, and a negative electrode current collector layer are laminated in this order, and an elastic spacer laminated in the stacking direction of the battery element, the power generating element expands and contracts in the stacking direction as the battery element is charged and discharged, and the elastic spacer contains fibers and has voids.

[0012] Generally, in a battery having a power generating element that expands and contracts in the stacking direction with charging and discharging, the deformation of the power generating element due to repeated charging and discharging can cause irreversible deformation of the members constituting the battery and peeling between the members, etc. Such deformation and peeling of the members can result in a decrease in the charge and discharge capacity due to, for example, an increase in internal resistance, etc.

[0013] In order to prevent the above problems, i.e., deformation and peeling of battery components, it is possible to arrange an elastic member in the direction in which the power generating element expands and contracts. However, if rubber is used as the elastic member, the internal pressure of the battery increases when the power generating element expands, and a sturdy container is required to withstand the pressure, resulting in a decrease in the energy density of the battery. In addition, if a spring, for example a disc spring, is used as the elastic member, the volume of the spring itself and the need for a spacer result in a decrease in the energy density of the battery.

[0014] In contrast, the battery of the present disclosure has an elastic spacer disposed in the direction in which the power generating element expands and contracts, and the elastic spacer contains fibers and has voids. Such an elastic spacer can apply pressure uniformly to the surface of the power generating element in the stacking direction and has a relatively wide elastic range. Therefore, the elastic spacer can elastically deform in response to the expansion and contraction of the power generating element due to repeated charging and discharging while suppressing problems that arise when rubber or springs are used.

[0015] In addition, as a battery having a power generating element that expands and contracts in the stacking direction with charging and discharging, for example, a lithium ion battery can be mentioned. Among lithium ion batteries, a lithium ion battery using an alloy-based active material as a negative electrode active material, or a lithium ion battery in which metallic lithium is precipitated between a solid electrolyte layer and a negative electrode current collector layer during discharging, has a particularly large expansion and contraction of the power generating element with charging and discharging, and when the battery of the present disclosure is such a battery, it is particularly useful.

[0016] Elastic spacer The elastic spacer is laminated in the lamination direction of the battery elements, that is, the elastic spacer is laminated on at least one surface of the positive electrode current collector layer or the negative electrode current collector layer of the battery elements.

[0017] The elastic spacer contains fibers and has voids. The fibers may be conductive. That is, the elastic spacer may be a conductive elastic spacer.

[0018] Examples of the fibers include carbon fibers and metal fibers. Metal fibers may be, for example, stainless steel (SUS), nickel, titanium, copper, or aluminum coated on a core material. Among them, carbon fibers are preferred. Carbon fibers have a relatively high elastic modulus, and are therefore particularly useful when the power generating element expands and contracts to a large extent. In addition, carbon fibers are very fine, and therefore an elastic spacer containing carbon fibers is useful because it can apply pressure particularly uniformly to a surface.

[0019] The elastic spacer may be, for example, a compression molded body of fibers.

[0020] From the viewpoint of improving the elasticity of the elastic spacer, the ratio of fibers to the solid content of the elastic spacer is preferably 90% by volume or more. The remainder may be, for example, a binder for bonding the fibers to form the elastic spacer.

[0021] The proportion of fibers in the solid content of the elastic spacer may be 90 vol % or more, 95 vol % or more, 97 vol % or more, or 99 vol % or more.

[0022] From the viewpoint of increasing the elastic range of the elastic spacer, it is preferable that the porosity of the elastic spacer is large, specifically, 60 to 80%.

[0023] The porosity of the elastic spacer may be 60% or more, 65% or more, or 70% or more, and may be 80% or less, 75% or less, or 70% or less.

[0024] From the viewpoint of improving the reversibility of the elastic spacer, the elastic range of the elastic spacer is preferably 0.1 or more.

[0025] The elastic range of the elastic spacer may be 0.1 or more, 0.2 or more, 0.3 or more, or 0.4 or more.

[0026] Battery element The battery element is formed by laminating a positive electrode current collector layer, a power generating element, and a negative electrode current collector layer in this order.

[0027] <Positive electrode current collector layer> The material used for the positive electrode current collector layer is not particularly limited, and any material that can be used for an all-solid-state battery can be appropriately used.

[0028] For example, the material used for the positive electrode current collector layer may be, but is not limited to, stainless steel (SUS), aluminum, copper, nickel, iron, titanium, carbon, etc. Among these, the material for the positive electrode current collector layer is preferably aluminum.

[0029] The shape of the positive electrode current collector layer is not particularly limited, and examples thereof include a foil shape, a plate shape, a mesh shape, etc. Among these, a foil shape is preferred.

[0030] <Power generation elements> The power generating element expands and contracts in the stacking direction as the power generating element is charged and discharged. Although not particularly limited, the expansion and contraction of the power generating element can be caused by, for example, the expansion and contraction of the active material accompanying the absorption / release of lithium of the active material accompanying the charge and discharge, or the precipitation of metallic lithium between the solid electrolyte layer and the negative electrode current collector layer.

[0031] Regarding the stacking direction of the battery of the present disclosure, the power generating element has a positive electrode layer, a solid electrolyte layer, and a negative electrode layer stacked in this order at least in a charged state.

[0032] (Positive electrode layer) The positive electrode layer contains a positive electrode active material and, optionally, a solid electrolyte, a conductive additive, and a binder.

[0033] The material of the positive electrode active material is not particularly limited. For example, the positive electrode active material may be lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMn2O4), LiCo 1 / 3 Ni 1 / 3 Mn 1 / 3 O2, Li 1+x Mn 2-x-y M y The material may be, but is not limited to, a Li-Mn spinel substituted with a different element having a composition represented by O4 (M is one or more metal elements selected from Al, Mg, Co, Fe, Ni, and Zn).

[0034] As the solid electrolyte, those described in the "(Solid electrolyte layer)" below may be appropriately used.

[0035] The conductive additive is not particularly limited. For example, the conductive additive may be a carbon material such as VGCF (Vapor Grown Carbon Fiber) and carbon nanofiber, a metal material, or the like, but is not limited thereto.

[0036] The binder is not particularly limited. For example, the binder may be, but is not limited to, a material such as polyvinylidene fluoride (PVdF), butadiene rubber (BR), polytetrafluoroethylene (PTFE), or styrene butadiene rubber (SBR), or a combination thereof.

[0037] (solid electrolyte layer) The solid electrolyte layer includes at least a solid electrolyte. In addition to the solid electrolyte, the solid electrolyte layer may include a binder, etc., as necessary. For the binder, the above description of "(positive electrode active material layer)" can be referred to.

[0038] The material of the solid electrolyte is not particularly limited, and any material that can be used as a solid electrolyte for an all-solid-state battery can be used. For example, the solid electrolyte may be, but is not limited to, a sulfide solid electrolyte, an oxide solid electrolyte, or a polymer electrolyte.

[0039] Examples of sulfide solid electrolytes include, but are not limited to, sulfide-based amorphous solid electrolytes, sulfide-based crystalline solid electrolytes, and argyrodite-type solid electrolytes. Specific examples of sulfide solid electrolytes include Li2S-P2S5-based (Li7P3S 11 , Li3PS4, Li8P2S9, etc.), Li2S-SiS2, LiI-Li2S-SiS2, LiI-Li2S-P2S5, LiI-LiBr-Li2S-P2S5, Li2S-P2S5-GeS2(Li 13 GeP3S 16 , Li 10 GeP2S 12 ), LiI-Li2S-P2O5, LiI-Li3PO4-P2S5, Li 7-x P.S. 6-x Cl x etc.; or combinations thereof, but are not limited to these.

[0040] An example of an oxide solid electrolyte is Li7La3Zr2O 12、 Li 7-x La3Zr 1-x Nb x O 12、 Li 7-3x La3Zr2Al x O 12 , Li 3x La 2 / 3-x TiO3, Li 1+x Al x Ti 2-x (PO4)3, Li 1+x Al x Ge 2-x (PO4)3, Li3PO4, or Li 3+x PO 4-x N x (LiPON), but is not limited to these.

[0041] The sulfide solid electrolyte and the oxide solid electrolyte may be glass or crystallized glass (glass ceramic).

[0042] Examples of the polymer electrolyte include, but are not limited to, polyethylene oxide (PEO), polypropylene oxide (PPO), and copolymers thereof.

[0043] (Negative electrode layer) The negative electrode layer contains a negative electrode active material and an optional solid electrolyte, a conductive additive, and a binder. Alternatively, the negative electrode layer may be a layer containing metallic lithium as a negative electrode active material that is deposited between the solid electrolyte layer and the negative electrode current collector layer in a charged state, and in this case, the negative electrode layer may disappear in a discharged state of the battery.

[0044] The material of the negative electrode active material is not particularly limited, and may be metallic lithium, or may be a material capable of absorbing and releasing metal ions such as lithium ions. Examples of the material capable of absorbing and releasing metal ions such as lithium ions include, but are not limited to, alloy-based negative electrode active materials and carbon materials.

[0045] The alloy-based negative electrode active material is not particularly limited, and examples thereof include Si alloy-based negative electrode active materials and Sn alloy-based negative electrode active materials. The Si alloy-based negative electrode active material includes silicon, silicon oxide, silicon carbide, silicon nitride, and solid solutions thereof. The Si alloy-based negative electrode active material can include elements other than silicon, such as Fe, Co, Sb, Bi, Pb, Ni, Cu, Zn, Ge, In, Sn, Ti, and the like. The Sn alloy-based negative electrode active material can include tin, tin oxide, tin nitride, and solid solutions thereof. The Sn alloy-based negative electrode active material can include elements other than tin, such as Fe, Co, Sb, Bi, Pb, Ni, Cu, Zn, Ge, In, Ti, Si, and the like. Among these, the Si alloy-based negative electrode active material is preferred.

[0046] The carbon material is not particularly limited, and examples thereof include hard carbon, soft carbon, graphite, and the like.

[0047] <Negative electrode current collector layer> The material and shape of the negative electrode current collector layer are not particularly limited, and the materials and shapes described in the above "Positive electrode current collector layer" may be used. In particular, the material of the negative electrode current collector layer is preferably copper. The shape is preferably a foil. EXAMPLES

[0048] Example 1 and Comparative Examples 1 and 2 Example 1 Vapor grown carbon fiber (VGCF) as fiber and polyvinylidene fluoride (PVdF) as binder were stirred in butyl butyrate and dried to obtain powder. 30 mg of the powder was placed in a metal cylinder and heated to 6 ton / cm. 2 The elastic spacer was formed by compression molding using a pressure of 1000.

[0049] A resin ring made of polyether ether ketone (PEEK) was placed in a ceramic cylinder. Then, inside the resin ring, a negative electrode current collector layer, a solid electrolyte layer, and LiNi as a positive electrode active material were placed. 1 / 3 Co 1 / 3 Mn 1 / 3 A positive electrode active material layer containing O2 and a positive electrode current collector layer were laminated in this order and uniaxially pressed to produce an all-solid-state battery inside the resin ring.

[0050] The solid-state battery was then punched out from the ceramic cylinder along with the resin ring.

[0051] The all-solid-state battery 2 used in the test had a configuration as shown in Figures 2 to 4. Figure 2 is a top view of the all-solid-state battery 2. Figure 3 is a cross-sectional side view of the all-solid-state battery 2 in a discharged state. Figure 4 is a cross-sectional side view of the all-solid-state battery 2 in a charged state.

[0052] 2 and 3, the all-solid-state battery 2 in a discharged state has a structure in which a positive electrode collector layer 10, a positive electrode active material layer 21, a solid electrolyte layer 22, and a negative electrode collector layer 30 are laminated in this order inside a resin ring 50. As shown in Fig. 4, when the all-solid-state battery 2 is charged, metallic lithium is precipitated between the solid electrolyte layer 22 and the negative electrode collector layer 30, and a negative electrode active material layer 23 is formed. In the all-solid-state battery 2, the negative electrode active material layer 23 disappears upon discharge and is formed upon charge.

[0053] As shown in the measuring device 3 in Fig. 5, a pin 100 was set above the all-solid-state battery 2, and the elastic spacer 40 and pin 110 prepared above were set below, and they were constrained to 0.2 N m using screws. A load cell 120 was placed on the upper pin 100, and a dynamic strain meter 130 and a data logger 140 were connected to the load cell 120 so that the pressure could be measured.

[0054] The charge and discharge test was performed by placing the measurement device 3 in which the all-solid-state battery 2 was placed in a thermostatic chamber at 60°C and charging and discharging the battery at a current value of 1.8 mA / cm 2 A charge / discharge test was performed in the voltage range of 3.0 to 4.2 V using a charge / discharge device HJ1001SD8 manufactured by Hokuto Denko Corporation.

[0055] Comparative Examples 1 and 2 A charge / discharge test was carried out in the same manner as in Example 1, except that a disc spring and rubber were used instead of the elastic spacer.

[0056] <result> The pressure before the charge / discharge test, the maximum pressure during the charge / discharge test, and the discharge capacity of the all-solid-state battery in each example are shown in Table 1.

[0057] [Table 1]

[0058] As shown in Table 1, in Example 1, which used an elastic spacer, the maximum pressure in the charge / discharge test was 3 MPa, and in Comparative Examples 1 and 2, which used a disc spring and rubber, the maximum pressures were 14 MPa and 10 MPa, respectively. [Explanation of symbols]

[0059] 1 solid state battery 10 Positive electrode current collector layer 20 Power generation elements 21 Cathode active material layer 22 Solid electrolyte layer 23 Negative electrode active material layer 30 Negative electrode current collector layer 40 Elastic spacer 2 All-solid-state battery 50 Resin Ring 3. Measuring Equipment 100 pins 110 pin 120 Load Cell 130 Dynamic strain meter 140 Data Logger

Claims

1. The battery includes a battery element in which a positive electrode current collector layer, a power generating element, and a negative electrode current collector layer are laminated in this order, and an elastic spacer is laminated in the lamination direction of the battery element, The power generating element expands and contracts in the stacking direction as the element is charged and discharged. The elastic spacer contains fibers and has voids, With respect to the stacking direction, the power generating element has a positive electrode layer, a solid electrolyte layer, and a negative electrode layer stacked in this order at least in a charged state, The elastic spacer is laminated on at least one surface of the battery element. battery.

2. 2. The battery according to claim 1, wherein the negative electrode layer contains lithium as a negative electrode active material that is deposited between the solid electrolyte layer and the negative electrode current collector layer in a charged state.

3. 3. The battery of claim 1 or 2, wherein the fibers are carbon fibers.

4. The battery according to claim 1 or 2, wherein the elastic spacer is a compression molded body of the fiber.

5. 3. The battery according to claim 1, wherein the ratio of the fibers to the solid content of the elastic spacer is 90% by volume or more.

6. 3. The battery according to claim 1, wherein the porosity of the elastic spacer is 60 to 80%.

7. 3. The battery of claim 1 or 2, which is a lithium ion battery.

Citation Information

Patent Citations

  • Bipolar battery, battery pack, and vehicle mounting them

    JP2007026734A

  • Battery module, battery pack, and vehicle with such batteries mounted thereon

    JP2007242593A

  • Separator for battery, and lithium secondary battery

    JP2008192483A

  • Lithium ion secondary battery

    JP2009181874A

  • Electrode active material layer for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery using the same

    JP2016207250A